Mathematical foundations of image processing and analysis - Pinoli, Jean-Charles (Digital signal and image processing series, 2014)
Filling a void in current literature, Mathematical Foundations of Image Processing and Analysis jointly addresses image processing and analysis, whereas most books on this topic solely focus on the processing aspects